The almost contract structures on hypersurfaces in four-dimensional centred biaffined space of elliptic and hyperbolic type - Kriščiūnaitė, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Л. Крищюнайте. Почти-контактные структуры на гиперповерхностях четырехмерного центробиаффинного пространства эллиптического и гиперболического типаA. Kriščiūnaitė. Beveik kontaktinės struktūros keturmatės centrobiafininės eliptinio ir hiperbolinio tipo erdvės hiperpaviršiuose